Spectral efficiency analysis and pilot reuse factor optimisation for multi‐cell massive SC‐SM MIMO. Issue 10 (21st May 2018) - Sun, Yue; Wang, Jintao; He, Longzhuang; Pan, Changyong; Ai, Bo; Song, Jian
Abstract : As a combination of spatial modulation (SM) system and massive multiple‐input multiple‐output (MIMO) system, massive SM aided MIMO (SM‐MIMO) system is recently proposed. In broadband scenarios, single‐carrier (SC) modulation is introduced to massive SM‐MIMO system, thus massive SC‐SM MIMO system is proposed for uplink multi‐user transmission over frequency‐selective fading channels. In this study, the uplink spectral efficiency (SE) of multi‐cell massive SC‐SM MIMO system is analysed, meanwhile the pilot contamination effect is taken into consideration. A tight SE lower bound of multi‐cell massive SC‐SM MIMO system is proposed with maximum ratio (MR) combining, which also takes into account the imperfect channel estimation, transmit antenna correlation and path loss. The tightness of the authors' proposed closed‐form SE lower bound is shown via simulation results. The optimal pilot reuse factor can be determined with different system configurations by simulations, and the pilot reuse factor that is larger than one is more suitable for less TAs and user equipments.